Nitric Oxide Sensing by a Blue Fluorescent Protein - Chiara Montali; Stefania Abbruzzetti; Arne Franzen; Giorgia Casini; Stefano Bruno; Pietro Delcanale; Sandra Burgstaller; Jeta Ramadani-Muja; Roland Malli; Thomas Gensch; Cristiano Viappiani (MDPI AG, 2022)
S-Nitrosylation of cysteine residues is an important molecular mechanism for dynamic, post-translational regulation of several proteins, providing a ubiquitous redox regulation. Cys residues are present in several fluorescent proteins (FP), including members of the family of Aequorea victoria Green Fluorescent Protein (GFP)-derived FPs, where two highly conserved cysteine residues contribute to a favorable environment for the autocatalytic chromophore formation reaction. The effect of nitric oxide on the fluorescence properties of FPs has not been investigated thus far, despite the tremendous role FPs have played for 25 years as tools in cell biology. We have examined the response to nitric oxide of fluorescence emission by the blue-emitting fluorescent protein mTagBFP2. To our surprise, upon exposure to micromolar concentrations of nitric oxide, we observed a roughly 30% reduction in fluorescence quantum yield and lifetime. Recovery of fluorescence emission is observed after treatment with Na-dithionite. Experiments on related fluorescent proteins from different families show similar nitric oxide sensitivity of their fluorescence. We correlate the effect with S-nitrosylation of Cys residues. Mutation of Cys residues in mTagBFP2 removes its nitric oxide sensitivity. Similarly, fluorescent proteins devoid of Cys residues are insensitive to nitric oxide. We finally show that mTagBFP2 can sense exogenously generated nitric oxide when expressed in a living mammalian cell. We propose mTagBFP2 as the starting point for a new class of genetically encoded nitric oxide sensors based on fluorescence lifetime imaging.